2017
DOI: 10.1159/000455917
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Effect of Flurbiprofen on Lithium Disposition in Rats

Abstract: Aims: Lithium is administered for treating bipolar disorders and is mainly excreted into urine. Nonsteroidal anti-inflammatory drugs inhibit this process. In this study, we examined the enantioselective effect of flurbiprofen on the disposition of lithium in rats. Methods: Pharmacokinetic experiments with lithium were performed. Results: Until 60 min after the intravenous administration of lithium chloride at 30 mg/kg as a bolus, 17.8% of lithium injected was recovered into the urine. Its renal clearance was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…The plasma concentrations of lithium were in the therapeutic range (Table 2). The renal clearance and the fractional excretion of lithium of the control group (Table 2) were comparable to our previous values that were obtained from the experiments with the lithium injection as a bolus [15,16]. Fanconi syndrome decreased the renal clearance of lithium, and no effect on the fractional excretion of lithium was recognized (Table 2).…”
Section: Discussion/conclusionsupporting
confidence: 85%
See 1 more Smart Citation
“…The plasma concentrations of lithium were in the therapeutic range (Table 2). The renal clearance and the fractional excretion of lithium of the control group (Table 2) were comparable to our previous values that were obtained from the experiments with the lithium injection as a bolus [15,16]. Fanconi syndrome decreased the renal clearance of lithium, and no effect on the fractional excretion of lithium was recognized (Table 2).…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…The correlation coefficient between creatinine clearance and lithium clearance of 303 data from 90 patients was calculated to be 0.4548 [25], and it is suggested that creatinine clear-ance may be a poor surrogate for the renal clearance of lithium exceptionally. In the previous and the present studies, we showed that the renal clearance of lithium was decreased by S-flurbiprofen, renal ischemia, and Fanconi syndrome in rats [15,16]. And, S-flurbiprofen decreased the fractional excretion of lithium, and no effect of renal ischemia and Fanconi syndrome on the ratio was recognized [15,16].…”
Section: Discussion/conclusionsupporting
confidence: 56%
“…This implies that the decline of the lithium reabsorption is not parallel with that of glomerular filtration in patients with renal failure. Our recent report indicated a decrease of the fractional excretion of lithium as well as C cr by (S)‐flurbiprofen in rats (Uwai et al, ). This suggests a lesser impairment of lithium reabsorption in comparison with the glomerular filtration in rats administered (S)‐flurbiprofen.…”
Section: Resultsmentioning
confidence: 92%
“…Recently, we examined the effect of each enantiomer of flurbiprofen, reported to increase the plasma concentration of lithium in patients with bipolar disorder (Hughes, Small, Brink, & McKenzie, ), on the renal handling of lithium in rats. The (S)‐enantiomer reduced creatinine clearance (C cr ) and the renal clearance of lithium (Li CL r ) in rats, and in particular, a significant decrease in the ratio of Li CL r to C cr was exhibited (Uwai, Matsumoto, Kawasaki, & Nabekura, ). The findings suggested that the damage to glomerular filtration by (S)‐flurbiprofen was greater than that to lithium reabsorption in the rats, and we considered it important to collect data regarding the renal handling of lithium in rats with various renal failures.…”
Section: Introductionmentioning
confidence: 99%
“…The ( S )-enantiomer of naproxen is commercially available. We examined the enantioselective effects of flurbiprofen on the disposition of lithium in rats, and demonstrated that the ( S )-enantiomer, but not the ( R )-enantiomer, decreased the renal clearance of lithium with the impairment of renal function [2]. The anticoagulant drug warfarin is also chiral.…”
Section: Introductionmentioning
confidence: 99%